Onsite investigation at a mail-order hatchery following a multistate Salmonella illness outbreak linked to live poultry—United States, 2018. (3rd October 2019) - Robertson, Scott A; Sidge, Jennifer L; Koski, Lia; Hardy, Margaret C; Stevenson, Lauren; Signs, Kimberly; Stobierski, Mary Grace; Bidol, Sally; Donovan, Danielle; Soehnlen, Marty; Jones, Kelly; Robeson, Sheri; et al.
ABSTRACT: Centers for Disease Control and Prevention (CDC ), health departments, and other state and federal partners have linked contact with live poultry to 70 human Salmonella outbreaks in the United States from 2000 to 2017, which resulted in a total of 4, 794 illnesses, 894 hospitalizations, and 7 deaths. During human salmonellosis outbreaks environmental sampling is rarely conducted as part of the outbreak investigation. CDC was contacted by state health officials on June 12, 2018, to provide support during an investigation of risk factors for Salmonella infections linked to live poultry originating at a mail-order hatchery. From January 1, 2018, to June 15, 2018, 13 human Salmonella infections in multiple states were attributed to exposure to live poultry from a single hatchery. Two serotypes of Salmonella were associated with these infections, Salmonella Enteritidis and Salmonella Litchfield. Molecular subtyping of the S. Enteritidis clinical isolates revealed they were closely related genetically (within 0 to 9 alleles) by core genome multi-locus sequence typing (cgMLST ) to isolates obtained from environmental samples taken from hatchery shipping containers received at retail outlets. Environmental sampling and onsite investigation of practices was conducted at the mail-order hatchery during an investigation on June 19, 2018. A total of 45 environmental samples were collected, and 4 (9%) grew Salmonella . A chick box liner from a box in the pre-shipping area yielded an isolate closely related to the S. Enteritidis outbreak strain (within 1 to 9 alleles by cgMLST). The onsite investigation revealed lapses in biosecurity, sanitation, quality assurance, and education of consumers. Review of Salmonella serotype testing performed by the hatchery revealed that the number of samples and type of samples collected monthly varied. Also, S. Enteritidis was identified at the hatchery every year since testing began in 2016. Recommendations to the hatchery for biosecurity, testing, and sanitation measures were made to help reduce burden of Salmonella in the hatchery and breeding flocks, thereby reducing the occurrence of human illness.